Multilayer coupled ring resonator filter for digital broadcasting applications: article / Mohd Ali Maghpur Muhammad - Muhammad, Mohd Ali Maghpur (2010)
A design of a multilayer microstrip bandpass filter based on coupled ring resonator is presented for digital satellite broadcasting applications. Centered at around 2.6 GHz with bandwidth of 4.2 % from 2.54 GHz to 2.65 GHz the filter is designed on a 0.75-mm-thick Rogers RO3003 substrate (εr = 3, tan δ = 0.0013). The Computer Simulation Technology (CST) simulator is used to design and simulate the response of the microstrip coupled ring resonator. Results from electromagnetic simulation of the filter involving return loss, S11 and insertion loss, S21 are presented through this paper.